2023
DOI: 10.3390/ijms24054542
|View full text |Cite
|
Sign up to set email alerts
|

Delayed TBI-Induced Neuronal Death in the Ipsilateral Hippocampus and Behavioral Deficits in Rats: Influence of Corticosterone-Dependent Survivorship Bias?

Abstract: Acute and chronic corticosterone (CS) elevations after traumatic brain injury (TBI) may be involved in distant hippocampal damage and the development of late posttraumatic behavioral pathology. CS-dependent behavioral and morphological changes were studied 3 months after TBI induced by lateral fluid percussion in 51 male Sprague–Dawley rats. CS was measured in the background 3 and 7 days and 1, 2 and 3 months after TBI. Tests including open field, elevated plus maze, object location, new object recognition tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…In this study, SB332235 was capable of ameliorating the neuronal damage and improved subsequent motor and cognitive de cits at 3 days post-injury. In parallel with previous studies [26, [33][34][35], our data showed that TBI caused pronouncedly higher mNSS score, reduction of time to maintain balance in beam-balance, enhancement in ambulatory time and a concomitant diminution in resting time in an open eld, and reduced discrimination index in novel object recognition task in animals, suggesting that TBI can trigger neurological de ciency, motor, and cognitive dysfunction. Of particular noteworthy, treatment with SB332235 potently reversed such de cits as shown by the lower mNSS score, elevation of time to maintain balance, decrease in ambulatory time and increase in resting time, and enhancement of discrimination index in TBI-exposed animals, indicative of a bene cial effect of SB332235 on the motor and memory impairments.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, SB332235 was capable of ameliorating the neuronal damage and improved subsequent motor and cognitive de cits at 3 days post-injury. In parallel with previous studies [26, [33][34][35], our data showed that TBI caused pronouncedly higher mNSS score, reduction of time to maintain balance in beam-balance, enhancement in ambulatory time and a concomitant diminution in resting time in an open eld, and reduced discrimination index in novel object recognition task in animals, suggesting that TBI can trigger neurological de ciency, motor, and cognitive dysfunction. Of particular noteworthy, treatment with SB332235 potently reversed such de cits as shown by the lower mNSS score, elevation of time to maintain balance, decrease in ambulatory time and increase in resting time, and enhancement of discrimination index in TBI-exposed animals, indicative of a bene cial effect of SB332235 on the motor and memory impairments.…”
Section: Discussionsupporting
confidence: 90%
“…For the higher cognitive function of the brain, cognitive impairment will occur in multiple parts of either side, especially in functional areas such as frontal lobe and hippocampus. [ 19 ] Studies have shown that the cognitive impairment is more severe, especially the damage in the frontal lobe. Executive functions in the frontal lobe include abstract ability, concept formation, selective memory, and cognitive transfer processes.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous activities of mice in EPM were recorded for 5 min by ANY‐Maze software. The travelled time in the open arms and the total travelled distance were recorded and analyzed 35 …”
Section: Methodsmentioning
confidence: 99%